Influence of residual mortar volume on the properties of recycled concrete aggregates. (1st October 2022) - Mazhoud, Brahim; Sedran, Thierry; Cazacliu, Bogdan; Cothenet, Alexis; Torrenti, Jean-Michel
Abstract: Recycled Concrete Aggregates (RCA) are mainly composed of two different materials: natural aggregate and attached mortar. Hence, RCA may have a much significant heterogeneity compared to natural aggregates. This heterogeneity limits their reuse in concrete due to the uncertainty in their expected behaviour. To clarify the effect of the attached paste volume on their properties, a single source of RCA was separated with a water jig according to the density of the particles. This original approach allows to avoid any disturbance of the data analysis with uncontrolled variation of paste nature or natural aggregate nature, as it is generally the case in literature collecting RCA from different sources. The used RCA had a narrow granular fraction (10–14 mm). After sorting tests, the sorted RCA was characterized by the measure of their density, water absorption, particle size distribution, particle shape and the attached mortar content. The results show that very large disparities exist in the density and the water absorption even in a narrow granular fraction, which can be explained by the dispersion of the attached mortar content in the RCA. These results allowed to established experimental relationships between the relative density and the others RCA properties. The developed relationships can been used to evaluate the attached mortar content for further laboratory study for example. Highlights: Recycled concrete aggregates (RCA) were finely sorted by density with a water jig and characterized. Even a narrow granular class of RCA can exhibit very large physical heterogeneities. Documented and educational demonstration of the sole role of the volume of residual mortar on the properties of RCAs. Equations relating the different properties of recycled aggregates (absorption, density, paste content …) are proposed. A thermogravimetric test to evaluate the paste content of RCA is proposed.